Life design facing the fertility gap: promoting gender equity to give women and men the freedom of a mindful life planning - Camussi, Elisabetta; Meneghetti, Daria; Rella, Riccardo; Sbarra, Maria Luisa; Calegari, Elena; Sassi, Cinzia; Annovazzi, Chiara (Frontiers in Psychology, 2023)
Nowadays, society is characterized by enormous and rapid changes, erratic careers, gender discrimination, injustices, and inequities. Discrimination includes professional and educational segregation, the gender pay gap, stereotypical gender roles, and social expectations. In this context, phenomena called low fertility and fertility gap are increasing. Indeed, the birth rate necessary to ensure the replacement of the population is not reached, with severe repercussions at a social, environmental, and economic level. This study aimed to investigate 835 women’s perceptions of the desire for motherhood and the associated difficulties. Hierarchical multiple regression and thematic decomposition analyses first highlight a significant difference between the number of children women realistically plan and the ideal number of children they would like. Secondly, the results showed how the parenthood choice is connected to the perception of social and gender inequity. Finally, in a Life Design perspective, preventive actions will be described to support women to get back to the center of life choices, building dignified fair paths and family projects.